Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1155/2014/875230
|View full text |Cite
|
Sign up to set email alerts
|

Butylidenephthalide Blocks Potassium Channels and Enhances Basal Tension in Isolated Guinea-Pig Trachea

Abstract: Butylidenephthalide (Bdph, 30~300 μM), a constituent of Ligusticum chuanxiong Hort., significantly enhanced tension in isolated guinea-pig trachea. In this study, we investigate the mechanism(s) of Bdph-induced contraction in the tissue. Isolated trachea was bathed in 5 mL of Krebs solution containing indomethacin (3 μM), and its tension changes were isometrically recorded. Cromakalim (3 μM), an ATP-dependent K+ channel opener, significantly antagonized the Bdph-induced enhancement of baseline tension. Bdph (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Recently, we reported Bdph similar to 4-AP, a blocker of K v 1 family of K + channels, to antagonize cromakalim, an ATP-dependent K + channel opener, in guinea-pig trachea (Hsu et al. 2014 ). Thus, Bdph may result in depolarization on the prejunctional membrane of adrenergic nerve ending, and in more releases of NA and ATP.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, we reported Bdph similar to 4-AP, a blocker of K v 1 family of K + channels, to antagonize cromakalim, an ATP-dependent K + channel opener, in guinea-pig trachea (Hsu et al. 2014 ). Thus, Bdph may result in depolarization on the prejunctional membrane of adrenergic nerve ending, and in more releases of NA and ATP.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, Bdph, similar to 4-aminopyridine (Hsu et al. 2014), a voltage-gated K + channel blocker (Choquet and Korn 1992) blocked voltage-gated K + channels to induce membrane depolarization and facilitation. In the present study, Bdph (100 μM) significantly increased the electrically stimulated release of NA from the tissue into the medium.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, we reported that Bdph similarly to 4-aminopyridine, a blocker of the Kv 1 family of K + channels, enhanced the baseline tension of the guinea-pig trachea (Hsu et al. 2014). The binding of Bdph to the K + channels of the smooth muscle cell membrane seems partially reversible, but the binding of Bdph to VDCCs seems irreversible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, when the K + channels were blocked and evoked prolonged repolarization, the nerve ending resulted in more excitability. Recently, we reported that Z-Bdph may be similar to 4-aminopiridine, a blocker of K v 1 family of K + channels, to enhance the baseline tension of guinea-pig trachea (Hsu et al 2014). There are two kinds of potassium channels, Kv1.3 and intermediate K + (IK) channel (K Ca 3.1), in T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%